Chedoke-McMaster attitudes towards children with handicaps scale for traditional sporting games (CATCH-TSG): initial validation in 7 different languages in adult and young populations - March-Llanes, Jaume; Mas-Ruiz, Lluis; Moya-Higueras, Jorge; Rius-Torrentó, Josep; Estrada-Plana, Veronica; Bañeres, Judit; Lavega-Burgués, Pere, The Opportunity Team, Spanish Opportunity Team; Camacho, R; Duran, C; Esperanza, M; et al. (Frontiers in Psychology, 2023)
Measuring attitudes towards disability is meant to assess which interventions are most likely to change population attitudes. Physical activities, such as Traditional Sporting Games, are an excellent methodology to fight against the stigma of disabled people. Thus, the main aim of this study was to validate the Chedoke-McMaster Attitudes Towards Children with Handicaps Scale (CATCH) adapted to a physical activity environment. Additionally, we implemented this process in a combined way, with 7 languages and 2 versions (adult and youth) simultaneously. The results showed that the CATCH-TSG scale provides the scientific community with a valid and reliable tool for professionals who want to assess the change in attitudes towards people with disabilities after receiving a psychoeducational intervention that includes physical activity (TSG). In addition, researchers will compare respective results from different countries and ages using different versions of the scale, jointly validated.